The impact of pulse generator longevity on the long-term costs of cardiac pacing. - Gillis AM; Macquarrie DS; Wilson SL (Pacing & Clinical Electrophysiology, 1996)
The long-term costs of cardiac pacing include the device costs, the procedural costs, the follow-up costs, and the replacement costs. At present, there is significant variability in the efficiencies of the integrated circuits and the total battery capacity among different pulse generators that will influence replacement rates over time. Accordingly, we compared the influence of pulse generator longevity on the long-term costs of pacing. The longevity of pulse generators was calculated based on the electrical characteristics of the device and the percentage of time the patient is paced. Replacement rates of pulse generators were estimated for our patient population over a 20-year period, based on patient survival and pulse generator longevity. The costs of pacing over this 20-year follow-up period were then calculated. The longevity of DDDR devices presently implanted in the United States ranges from 8-14 years, assuming that patients are paced 50% of the time. Replacement rates in this population over a 20-year follow-up period were calculated to range from 0.34-0.66, and the total costs of pacing would range from $11,898-14,900 per patient. The longevity of SSIR devices ranges from 7-20 years, assuming that patients are paced 50% of the time. Replacement rates were calculated over the 20-year follow-up period to range from 0.20-0.84, and the total costs of VVIR pacing would range from $8,331-i 3,286. Based on the proportion of pulse generator models implanted in patients in the United States, the maximum cost differential to the health care system is approximately $424 million/year comparing the devices with the shortest and greatest longevities. Thus, pulse generator longevity may significantly influence the long-term costs of pacing. Patient survival and pulse generator system longevity should be considered when selecting the appropriate pacing system for the individual patient.